(Cryo)Transmission Electron Microscopy of Phospholipid Model Membranes Interacting with Amphiphilic and Polyphilic Molecules - Meister, Annette (Polymers (Basel), 2017)
Lipid membranes can incorporate amphiphilic or polyphilic molecules leading to specific functionalities and to adaptable properties of the lipid bilayer host. The insertion of guest molecules into membranes frequently induces changes in the shape of the lipid matrix that can be visualized by transmission electron microscopy (TEM) techniques. Here, we review the use of stained and vitrified specimens in (cryo)TEM to characterize the morphology of amphiphilic and polyphilic molecules upon insertion into phospholipid model membranes. Special emphasis is placed on the impact of novel synthetic amphiphilic and polyphilic bolalipids and polymers on membrane integrity and shape stability.